Feeding fermented palm kernel cake with higher levels of dietary fat improved gut bacterial population and blood lipid concentration but not the growth performance in broiler chickens - Hakim, Ali Hanafiah (Taylor & Francis, 2021)
The study aimed to determine the effects of Weisella confusa SR-17b fermented PKC (LPKC) and different levels of dietary fats on the growth performance, caecal microbial population, and blood lipid profile concentration in broiler chickens raised in the tropical environment. During the starter period, all birds received the same basal diet. From d 22 to 35, broiler chickens were randomly fed with either (1) 20% LPKC based diet with 5% palm oil, (2) 20% LPKC-based diet with 9.5% palm oil, (3) 20% PKC-based diet with 5% palm oil or (4) 20% PKC-based diet with 9.5% palm oil.No significant difference was observed between LPKC and PKC diets on broilers' growth performance. LPKC-based diet reduced the caecal population of E. coli and serum triglyceride concentration. In terms of oil supplementation, both PKC- and LPKC-based diets required higher levels of dietary fat to maintain optimum growth performance. A higher level of dietary fat in the LPKC-/PKC-based diet reduced serum levels of triglycerides and lower-density lipoprotein cholesterol and lowered the caecal E. coli population.